Pagando na mesma moeda : metáfora da contabilidade moral em textos medievais ingleses - Martinho, Leonardo Nazar (2013)
This dissertation is aimed at verifying the experiential motivation of metaphorical language in diachronic perspective. More specifically, we have tried to identify how specific socio-historical-cultural conditions may affect the actualization of a metaphor. To this end, we have grounded this research on the Conceptual Metaphor Theory, which presents the linguistic metaphors in language as resulting from a conceptual-level mapping between domains of knowledge. With this in mind, we have restricted our investigation to the evidences of the MORAL ACCOUNTING METAPHOR in medieval religious instruction texts in England. Linguistic evidences of this metaphor in the Early and High Middle Ages were extracted and aspects of MORAL INTERACTION they express were identified, tabulated and confronted. Lastly, we have sought explanations for the maintenance and variation in the actualization of the metaphor both in the immediate context of doctrinal production and in broader context of commercial practices. We have found that, side by side with the structural stability provided by a general Equivalent Exchange scheme, there is evidence of the highlighting of aspects of MORAL INTERACTION that are situated historically e discursively.